Genetic polymorphisms in SLC5A2 are associated with clinical outcomes and dapagliflozin response in heart failure patients - Abou Warda, Ahmed Essam; Flohr, Rylie M.; Sarhan, Rania M.; Salem, Mohamed Nabil; Salem, Heba F.; Moharram, Ayman N.; Alanazi, Abdullah S.; Lteif, Christelle; Gawronski, Brian E.; Dumeny, Leanne; Alsahli, Tariq G.; Elenizi, Khaled; et al. (Frontiers in Pharmacology, 2025)
BackgroundSodium-glucose cotransporter-2 inhibitors (SGLT2i) have emerged as promising therapeutics for heart failure (HF). Nevertheless, evidence supporting the mechanism of SGLT2i efficacy in HF patients is currently limited. Genetic variation in SLC5A2 (encoding SGLT2) may influence HF progression and SGLT2i response, as well as inform potential SGLT2i mechanisms. Thus, this study investigated associations between SLC5A2 variation and clinical outcomes in SGLT2i-naïve and dapagliflozin-treated HF cohorts.MethodsWe analyzed two HF cohorts to identify variants associated with SGLT2i response pathways. Adjusted Cox proportional-hazard regression models were used to assess the effect of SLC5A2 variation on a primary composite outcome of cardiovascular (CV) hospitalization or all-cause mortality in SGLT2i-naïve patients, and HF hospitalization or CV death in dapagliflozin-treated patients. The initial cohort comprised 327 American HF patients naïve to SGLT2i throughout the study. Subsequently, a prospective cohort study of 190 Egyptian SGLT2i-naïve HF patients treated with dapagliflozin was analyzed. In this cohort, SNPs in UGT2B4 and SLC2A1 were also investigated. Changes in NT-proBNP levels, KCCQ-12 scores, echocardiographic parameters, and eGFR throughout 6-month follow-up were tested with linear regression models as secondary outcomes.ResultsIn SGLT2i-naïve patients, rs3813008 (SLC5A2) was significantly associated with reduced risk of the composite outcome of all-cause death or hospitalization (HR = 0.65, 95% CI: 0.47–0.89, P = 0.008). In the dapagliflozin-treated cohort, rs3813008 was also associated with death or hospitalization, but with increased risk in treated patients (HR = 3.38, 95% CI: 1.35–8.42, P = 0.008).ConclusionOur study suggests that SLC5A2 variation is associated with clinical outcomes in SGLT2i-naïve and treated HF patients, warranting further investigation of SLC5A2 and SGLT2i interactions.